Efficacy and tolerability of anti-programmed death-ligand 1 (PD-L1) antibody (Avelumab) treatment in advanced thymoma. Issue 1 (21st October 2019) - Rajan, Arun; Heery, Christopher R.; Thomas, Anish; Mammen, Andrew L.; Perry, Susan; O'Sullivan Coyne, Geraldine; Guha, Udayan; Berman, Arlene; Szabo, Eva; Madan, Ravi A.; Ballester, Leomar Y.; Pittaluga, Stefania; et al.
Abstract : Background: Thymic epithelial tumors are PD-L1–expressing tumors of thymic epithelial origin characterized by varying degrees of lymphocytic infiltration and a predisposition towards development of paraneoplastic autoimmunity. PD-1–targeting antibodies have been evaluated, largely in patients with thymic carcinoma. We sought to evaluate the efficacy and safety of the anti-PD-L1 antibody, avelumab (MSB0010718C), in patients with relapsed, advanced thymic epithelial tumors and conduct correlative immunological studies. Methods: Seven patients with thymoma and one patient with thymic carcinoma were enrolled in a phase I, dose-escalation trial of avelumab (MSB0010718C), and treated with avelumab at doses of 10 mg/kg to 20 mg/kg every 2 weeks until disease progression or development of intolerable side effects. Tissue and blood immunological analyses were conducted. Results: Two of seven (29%) patients with thymoma had a confirmed Response Evaluation Criteria in Solid Tumors–defined partial response, two (29%) had an unconfirmed partial response and three patients (two thymoma; one thymic carcinoma) had stable disease (43%). Three of four responses were observed after a single dose of avelumab. All responders developed immune-related adverse events that resolved with immunosuppressive therapy. Only one of four patients without a clinical response developed immune-related adverse events. Responders had a higher absolute lymphocyte count, lower frequencies of B cells, regulatory T cells, conventional dendritic cells, and natural killer cells prior to therapy. Conclusion: These results demonstrate anti-tumor activity of PD-L1 inhibition in patients with relapsed thymoma accompanied by a high frequency of immune-related adverse events. Pre-treatment immune cell subset populations differ between responders and non-responders. Trial registration: ClinicalTrials.gov - NCT01772004 . Date of registration – January 21, 2013.